2008
DOI: 10.1161/hypertensionaha.107.096487
|View full text |Cite
|
Sign up to set email alerts
|

G Protein–Coupled Receptor Kinase 4

Abstract: N early 30% of middle-aged Americans have hypertension, but the prevalence is higher in non-Hispanic blacks and individuals Ͼ60 years of age (65%). 1 There is a direct and quantitative relationship between higher blood pressure values and mortality. Although 30% to 50% is thought to be heritable, the genetic cause(s) of essential hypertension has been difficult to identify. More than 1 gene is undoubtedly involved, because Mendelian dominant and recessive traits are not readily discernible in hypertensive subj… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
30
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…GRK4 variants, including 65L, 142V, and 486V, by themselves, or interaction with other variants of other genes are associated with hypertension in American Caucasians 39 , Australian Caucasians 12 , Italians 36 and northern Han Chinese 40 . We have reported that hGRK4γ 142V transgenic mice on 98% C57BL/6J background are hypertensive relative to non-transgenic littermates and hGRK4γ WT transgenic mice 6,8,11,13,34 . To further investigate the role of GRK4 variants on the hypertension, we generated hGRK4γ 142V and GRK4γ WT transgenic mice on C57BL/6J and SJL/J background.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…GRK4 variants, including 65L, 142V, and 486V, by themselves, or interaction with other variants of other genes are associated with hypertension in American Caucasians 39 , Australian Caucasians 12 , Italians 36 and northern Han Chinese 40 . We have reported that hGRK4γ 142V transgenic mice on 98% C57BL/6J background are hypertensive relative to non-transgenic littermates and hGRK4γ WT transgenic mice 6,8,11,13,34 . To further investigate the role of GRK4 variants on the hypertension, we generated hGRK4γ 142V and GRK4γ WT transgenic mice on C57BL/6J and SJL/J background.…”
Section: Discussionmentioning
confidence: 99%
“…The GRK4 locus (4p16.3) is linked to and GRK4 gene variants are associated with human essential hypertension 4,6,8,11,12,[36][37][38] . In Ghanaians, the two-locus model of angiotensin converting enzyme I/D and GRK4 65L predicts the hypertensive phenotype 70.5% of the time 37 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This may also be true for D 3 R. The requirement for GRK4, in its capacity to phosphorylate and/or properly position the receptor in the membrane, may explain the inhibitory effect of heparin or of decreased GRK4 expression on D 3 R-induced mitogenesis and also opens new views into the role of receptor phosphorylation on signal transduction. However, persistently increased constitutive GRK4 activity results in desensitization of D 1 R, seen in human essential hypertension (1,13,17). Whether a similar state occurs with the D 3 R remains to be determined.…”
Section: Discussionmentioning
confidence: 99%